2018
DOI: 10.1371/journal.pone.0194809
|View full text |Cite|
|
Sign up to set email alerts
|

Hedgehog inhibition mediates radiation sensitivity in mouse xenograft models of human esophageal adenocarcinoma

Abstract: BackgroundThe Hedgehog (Hh) signaling pathway is active in esophageal adenocarcinoma (EAC). We used a patient-derived murine xenograft (PDX) model of EAC to evaluate tumour response to conventional treatment with radiation/chemoradiation with or without Hh inhibition. Our goal was to determine the potential radioresistance effects of Hh signaling and radiosensitization by Hh inhibitors.MethodsPDX models were treated with radiation, chemotherapy or combined chemoradiation. Tumour response was measured by growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
3
12
0
Order By: Relevance
“…Some scholars demonstrated that the expression of SHH are associated with the survival outcome of the neoadjuvant chemoradiotherapy (nCRT) in patients with ESCC, and the expression of PTCH1 and Gli1 may be significantly associated with ESCC resistance to chemoradiotherapy . Furthermore, inhibition of Hedgehog signaling can regulate radiation sensitivity in mouse xenograft models of human esophageal cancer . So, targeting the SHH pathway may become a novel approach to prevent or inhibit the progression of ESCC, this is consistent with our point of view.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Some scholars demonstrated that the expression of SHH are associated with the survival outcome of the neoadjuvant chemoradiotherapy (nCRT) in patients with ESCC, and the expression of PTCH1 and Gli1 may be significantly associated with ESCC resistance to chemoradiotherapy . Furthermore, inhibition of Hedgehog signaling can regulate radiation sensitivity in mouse xenograft models of human esophageal cancer . So, targeting the SHH pathway may become a novel approach to prevent or inhibit the progression of ESCC, this is consistent with our point of view.…”
Section: Discussionsupporting
confidence: 86%
“…51 Furthermore, inhibition of Hedgehog signaling can regulate radiation sensitivity in mouse xenograft models of human esophageal cancer. 52 So, targeting the SHH pathway may become a novel approach to prevent or inhibit the progression of ESCC, this is consistent with our point of view. In our study, we found that inhibiting the exosomal transfer of SHH from CAFs to cancer cells can influence the progression of ESCC in vivo and in vitro.…”
Section: Te-1supporting
confidence: 90%
“…In vivo inhibition of Shh pathway by Gli antagonist (GANT61), a Smo-inhibitor, has synergistic effect with radiotherapy in xenograft model of prostate cancer [ 144 ]. A monoclonal anti-Shh antibody, 5E1 or LED225 (Novartis) was able to increase the efficacy of radiation treatment in patient-derived xenograft models of cervical and esophageal cancer [ 145 , 146 ]. Clinically, expression of Shh pathway (Gli1 staining) was associated with the efficacy of esophageal patients treated with chemoradiation and surgery, in two cohorts of patients ( n = 60 and n = 167) [ 147 ].…”
Section: Shh Pathway and Resistance To Radiotherapymentioning
confidence: 99%
“…Treatment of TNBC relies on DNA-damaging agents, including conventional chemotherapy and IR ( 30 ). Though inhibiting Hh has been shown to sensitize cancer cells to genotoxic therapies, the underlying mechanisms to this point have remained vague ( 12 , 13 ). Our study has uncovered an unexpected role for Hh signaling in the repair of damaged rDNA that helps to explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that GLI1 upregulates expression of NER and BER genes in response to SSBs to facilitate their repair ( 11 ). Hh inhibition is also known to sensitize cancer cells to agents that induce DSBs, but the mechanisms by which Hh influences DSB repair are poorly understood ( 12 , 13 ). We hypothesized that induction of DSBs by ionizing radiation (IR) would result in cistromic changes in GLI1 in order to orchestrate the activation of DNA repair programs.…”
Section: Introductionmentioning
confidence: 99%